2021
DOI: 10.1073/pnas.2025435118
|View full text |Cite
|
Sign up to set email alerts
|

Coral bleaching response is unaltered following acclimatization to reefs with distinct environmental conditions

Abstract: Urgent action is needed to prevent the demise of coral reefs as the climate crisis leads to an increasingly warmer and more acidic ocean. Propagating climate change–resistant corals to restore degraded reefs is one promising strategy; however, empirical evidence is needed to determine whether stress resistance is affected by transplantation beyond a coral’s native reef. Here, we assessed the performance of bleaching-resistant individuals of two coral species following reciprocal transplantation between reefs w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 80 publications
2
24
0
Order By: Relevance
“…While individual genotypes of some species might be resilient to repeated warming, experimentally subjecting corals to simulated stress events in order to stress harden them to future warming or to select those individuals most likely to be “winners” appears not to be a practical strategy. This conclusion is corroborated by Barott et al (2021) who likewise recently found no alteration of bleaching response among preconditioned corals in a reciprocal transplant experiment in Kāne‘ohe Bay. Taken together, thermally preconditioning or stress hardening corals would likely also not transfer to future generations.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…While individual genotypes of some species might be resilient to repeated warming, experimentally subjecting corals to simulated stress events in order to stress harden them to future warming or to select those individuals most likely to be “winners” appears not to be a practical strategy. This conclusion is corroborated by Barott et al (2021) who likewise recently found no alteration of bleaching response among preconditioned corals in a reciprocal transplant experiment in Kāne‘ohe Bay. Taken together, thermally preconditioning or stress hardening corals would likely also not transfer to future generations.…”
Section: Discussionsupporting
confidence: 67%
“…Examinations of nursery and restored A. cervicornis have suggested the fastest growing genotypes of restored colonies might trade growth for thermal stress recovery ( Ladd et al, 2017 ), a potential tradeoff of skeletal density with branch extension ( Lohr & Patterson, 2017 ), and growth alone when moved from nursery to reef was not predictive of success ( O’Donnell et al, 2018 ). Additionally, based on the outcome of this study and ( Barott et al, 2021 ) the time, effort, and increased expense of thermal preconditioning to promote stress hardening is not warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Because relatively few genets were shared between nurseries it is hard to generalize from these results. However, reciprocal transplant studies have shown that corals typically maintain similar thermal tolerance even after being moved to a new environment [13,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Following translocation, it is anticipated that transplants interbreed with the native population and that heat tolerance alleles will be incorporated into the native genetic background. Translocation can be achieved with both early life stages or adults, within a reef [28], to a nearby reef [29][30][31] or over larger distances within [32] or between regions [33]. Findings so far suggest transplants largely retain the tolerance ranking exhibited at their native reef site.…”
Section: Manipulations Targeted At the Coral Hostmentioning
confidence: 90%